2016
DOI: 10.1063/1.4966126
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric performance of SnSe based composites with carbon black nanoinclusions

Abstract: Recently, a single crystalline SnSe and its sodium doped compound are reported to have an ultralow thermal conductivity and a high thermoelectric figure of merit. However, the highest thermoelectric figure of merit for polycrystalline SnSe-based materials is not larger than 1. In this study, we report a high thermoelectric figure of merit 1.21 at 903 K for poly-crystalline SnSe, realized by incorporating a proper proportion of carbon black as nano-inclusions. The exceptional performance arises from the enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…The introduction of appropriate inclusions in polycrystalline SnSe can achieve a high peak ZT in SnSe system [84,276]. Many different types of inclusion, such as second phase (SnSe 2 [84] and Se nanowires [297]), nanoprecipitates (rock-salt-type SnSe [141] and Sn oxides [67]), simple substance (carbon black nanoinclusions [298]), compounds (SnS [129,299], 2D-MoSe 2 [300]) and compounds (SiC [259] and PbTe [301] SnS [257]. SnSe can also be treated as inclusion in other thermoelectric materials systems, such as (Cu 2 Se) 0.97 (SnSe) 0.03 [303], and (PbSe) 0.9 (SnSe) 0.1 [257].…”
Section: Inclusionsmentioning
confidence: 99%
“…The introduction of appropriate inclusions in polycrystalline SnSe can achieve a high peak ZT in SnSe system [84,276]. Many different types of inclusion, such as second phase (SnSe 2 [84] and Se nanowires [297]), nanoprecipitates (rock-salt-type SnSe [141] and Sn oxides [67]), simple substance (carbon black nanoinclusions [298]), compounds (SnS [129,299], 2D-MoSe 2 [300]) and compounds (SiC [259] and PbTe [301] SnS [257]. SnSe can also be treated as inclusion in other thermoelectric materials systems, such as (Cu 2 Se) 0.97 (SnSe) 0.03 [303], and (PbSe) 0.9 (SnSe) 0.1 [257].…”
Section: Inclusionsmentioning
confidence: 99%
“…Similarly, a very low lattice thermal conductivity of SnSe makes a good zT of 1.1 at 773 K . Textured SnSe polycrystals with a good thermoelectric behavior were reported by Li et al Similarly, a high thermoelectric zT of 1.21 at 903 K has been realized in SnSe by incorporation of a proper fraction of carbon black as nanoinclusions …”
Section: Introduction To Thermoelectricsmentioning
confidence: 69%
“…Although the presence of the grain boundaries and MWCNT/(Bi 0.2 Sb 0.8 ) 2 Te 3 interfaces resulted in extra scattering of the carriers and hence reduced electrical conductivity, the overall improvement is attributed mainly to the reduction of thermal conductivity as a result of strong phonon scattering. Li et al [178] reported a high figure of merit of 1.21 for polycrystalline p-type SnSe when incorpo- rated with 2.5 vol% of carbon black. The improvement is attributed mainly to the increase in electrical conductivity resulting in a high power factor.…”
Section: Carbon-based Layered Materials Compositesmentioning
confidence: 99%